Henoch-Schönlein purpura associated with Strongyloides stercoralis infection - Janković, Sveta S; Nikolić, Marijana; Simović, Aleksandra; Vujić, Ana (Vojnosanitetski pregled, 2017)
Introduction. Henoch-Schönlein purpura (HSP) is a small blood vessel vasculitis, which usually manifests during childhood. The exact cause of the disease is unknown. Case report. We reported a 14-year-old girl who had been admitted to our clinic due to the appearance of red macules on her extremities and face, vomiting, and pain in the abdomen and joints. The patient was initially diagnosed with Henoch-Schönlein purpura. At the end of the fourth week of illness, larvae of Strongyloides stercoralis were detected in stool samples. The patient was therefore treated with mebendazole, after which all symptoms permanently withdrew. About a month later laboratory examinations were repeated demonstrating increasing signs of renal damage. Kidney biopsy was performed, showing mesangioproliferative glomerulonephritis with crescents and IgA and C3 positive staining in the mesangium. Upon reviewing the clinical presentation, biochemically demonstrated progressive renal damage and biopsy results, the patient was diagnosed with HSP nephritis. Conclusion. The time course of the disease and present knowledge concerning the pathogenic mechanisms of HSP suggest that Strongyloides stercoralis infection could have caused HSP in the presented patient, which was complicated by nephritis.